CCR 20(th) Anniversary Commentary: Autologous T Cells—The Ultimate Personalized Drug for the Immunotherapy of Human Cancer - Rosenberg, Steven A. (Clin Cancer Res, 2015)
The article by Rosenberg and colleagues, which was published in the July 1, 2011, issue of Clinical Cancer Research, demonstrated the power of the adoptive transfer of autologous antitumor T cells to mediate the complete, durable, and likely curative regression of cancer in patients with heavily pretreated metastatic melanoma. It also provided a stimulus to the development of cell transfer approaches for other cancer types using both natural and genetically engineered lymphocytes.